Visible‐Light‐Driven Water Oxidation on a Photoanode by Supramolecular Assembly of Photosensitizer and Catalyst. Issue 10 (6th October 2016) - Li, Hua; Li, Fei; Wang, Yong; Bai, Lichen; Yu, Fengshou; Sun, Licheng
Abstract: A ruthenium water oxidation catalyst (WOC) bearing hydrophobic ligands was incorporated on the surface of a dye‐sensitized nanostructured TiO2 film by formation of a host–guest adduct with the dye. This provides a new strategy for constructing photocatalytically active electrodes for water oxidation. The resultant photoanode exhibits a photocurrent of 800 μA cm −2 under visible‐light illumination (λ>400 nm, 300 mW cm −2 ) and 240 μA cm −2 under simulated sunlight illumination (AM 1.5G, 100 mW cm −2 ) with an applied bias of 0.2 V vs. NHE in neutral phosphate buffer. Abstract : A "take‐charge" guest : A ruthenium water oxidation catalyst was incorporated on the surface of a dye‐sensitized nanostructured TiO2 film when it formed a host–guest adduct with the chromophore, providing a new strategy for photoanode construction.